Pengaruh Penggunaan Game Edukasi Wordwall terhadap Minat Belajar Bahasa Inggris Siswa Kelas VII - Vaness J.X. Gerungai; Tellma M. Tiwa; Gloridei L. Kapahang (Paedagogie, 2026)
This study aims to determine the effect of using the Wordwall educational game on English learning interest in seventh-grade students of SMP Negeri 2 Tomohon. Considering the importance of learning interest in increasing student motivation and engagement in learning, the use of technology-based learning media, such as educational games, is an attractive alternative. This study used a quasi-experimental design with the experimental group given learning using the Wordwall educational game and the control group given conventional learning. Data collection methods were carried out through pre-tests and post-tests using a Likert-scale English learning interest questionnaire. The results of the analysis showed that although there was a tendency for increased learning interest in the experimental group, the difference between the two groups was not statistically significant at the α = 0.05 level. However, the calculated effect size (Cohen's d) showed that the use of Wordwall had a small to moderate effect on increasing English learning interest. This study suggests that educational games such as Wordwall can be an effective learning medium in increasing students' interest in learning with more consistent and sustainable use in the learning process.